2011
DOI: 10.1108/17538371111144201
|View full text |Cite
|
Sign up to set email alerts
|

Exploring infrastructure procurement by Australian state governments

Abstract: PurposeThe purpose of this paper is to report on a research thesis that explores how Australian state government agencies procure infrastructure projects and the extent to which they view the procurement process as an opportunity to deliver more than just a physical facility. The primary purpose of this study was to understand the practice of construction project procurement by project managers on behalf of Australian state government agencies and to explore the creation of public value through procurement.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This can be improved if the involved stakeholders are aware of barriers and drivers to the adoption of SID. While numerous Australian studies have been conducted around sustainability and infrastructure development, recent ones focus on infrastructure procurement [5], social infrastructure in the areas of PPPs [6], development of sustainability reporting tools [7], and sustainable management through decision-making tools [8]. However, there is an obvious omission of South Australian and construction-specific studies.…”
Section: Introductionmentioning
confidence: 99%
“…This can be improved if the involved stakeholders are aware of barriers and drivers to the adoption of SID. While numerous Australian studies have been conducted around sustainability and infrastructure development, recent ones focus on infrastructure procurement [5], social infrastructure in the areas of PPPs [6], development of sustainability reporting tools [7], and sustainable management through decision-making tools [8]. However, there is an obvious omission of South Australian and construction-specific studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a suggestion that the focus is changing, with 43.48% of BS staff stating that quality was also a consideration. Whilst this is representative of the responsibility to stewardship of public funds that such organizations face, it also reflects observations that public‐sector organizations are still cost focused (McIvor et al ., 2002; Staples and Dalrymple, 2011).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Many authors agree that procurement has become increasingly valued at the corporate level, with some suggesting that it should be considered equally important as other strategic functions such as marketing, finance, and operations (McIvor et al ., 1997; Cavinato, 1999; Rink and Fox, 1999; Paulraj et al ., 2006). Despite this, it has been observed that public procurement is still focused on reducing transaction costs and fails to consider the total acquisition costs of products (Staples and Dalrymple, 2011).…”
Section: Public‐sector Procurementmentioning
confidence: 99%
“…Many authors agree that procurement has become increasingly recognized at the corporate level with some suggesting that it should be considered equally important like other strategically significant functions such as marketing, finance, and operations [Paulraj et al, 2006;Cavinato, 1999;Rink, Fox, 1999;McIvor et al, 1997]. Despite this, it has been observed that public sector procurement is still focused on reducing transaction costs and fails to consider the total acquisition costs of products [Staples, Dalrymple, 2011].…”
Section: Public and Private Sector Strategic Procurementmentioning
confidence: 99%